Analisis Kelayakan Usahatani Kakao Pada Kelompok Tani Prima Jaya di Desa Pelambaian Kecamatan Tapung - Cindy Frisca; Evy Maharani; Yusmini Yusmini (Jurnal Sosial Ekonomi Pertanian, 2022)
This study aims to analyze the financial feasibility and sensitivity to changes in input prices, output prices and the amount of production of cocoa farmers in the Prima Jaya Farmers Group. Prima Jaya Farmers Group is a cocoa farmer group that was formed in 2016. This research uses a case study method, the research data consists of primary data and secondary data. The feasibility data analysis was carried out using three investment criteria, namely Net Presen Value (NPV), Net Benefit Cost Ratio (Net B/C), Internal Rate of Return (IRR). The results of the study concluded that the business activities carried out by farmers in the Prima Jaya Farmer Group were financially feasible, this was indicated by a positive NPV value of Rp. 105.097.456. The IRR value is higher than the discount rate, which is 26.65%, the Net B/C value is 3,70. The results of the sensitivity analysis based on changes in input prices by 10%, a decrease in the price of cocoa beans by 49,21% and a decrease in the amount of cocoa production by 49,15% indicate that cocoa farming carried out by farmers in the Prima Jaya Farmer Group is still financially feasible.